2022
DOI: 10.1108/ecam-10-2021-0855
|View full text |Cite
|
Sign up to set email alerts
|

Risk allocation and benefit distribution of PPP projects for construction waste recycling: a case study of China

Abstract: PurposePublic-private partnership (PPP) projects for construction waste recycling have become the main approach to construction waste treatment in China. Risk sharing and income distribution of PPP projects play a vital role in achieving project success. This paper is aimed at building a practical and effective risk sharing and income distribution model to achieve win–win situation among different stakeholders, thereby providing a systematic framework for governments to promote construction waste recycling.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 82 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…At the same time as Wang, Z.S. et al [53] found that government departments and social capital sectors can gain more benefits after adopting the cooperative model. The same is true for the general contractor and subcontractor; both of them can only cooperate to obtain the maximum benefit, and the optimal outcome of both sides of the game many times is cooperation [54], which is consistent with reality.…”
Section: Discussionmentioning
confidence: 89%
“…At the same time as Wang, Z.S. et al [53] found that government departments and social capital sectors can gain more benefits after adopting the cooperative model. The same is true for the general contractor and subcontractor; both of them can only cooperate to obtain the maximum benefit, and the optimal outcome of both sides of the game many times is cooperation [54], which is consistent with reality.…”
Section: Discussionmentioning
confidence: 89%
“…BWM, a multi-criterion decision-making method 29 , is employed to determine the weights of a set of criteria or factors, providing clarity on their impact in decision-making problems. This method offers the advantage of yielding consistent results with minimal comparative information and has found widespread application in project selection 30 , supplier evaluation 31,32 , investment decisions, determining the appropriate location in the field of clean energy 33 , equipment selection 34 , project subcontracting 35,36 , etc. By integrating the BWM with the FCE, we formulated an evaluation model capable of considering quantitative factors, making it suitable for the intricate and multidisciplinary nature of DT platforms.…”
Section: Bwm-fce Evaluation Modelmentioning
confidence: 99%
“…Reasons why a mature CDW recycling market mechanism cannot be formed [26,27] Channels for solving CDW resource problems [28,29] Research status of CDW recycling PPP projects [30][31][32][33][34] Compensation mechanism during PPP projects operation period…”
Section: Cdw Recycling Ppp Projectsmentioning
confidence: 99%
“…On the one hand, most studies have considered the risk-sharing mechanism, income distribution model, public supervision, and government reward and punishment system and support policies of CDW recycling PPP projects [30,31]. Unfortunately, the exist-ing research does not focus on the performance of CDW resourceful PPP projects in the operation stage.…”
Section: Cdw Recycling Ppp Projectsmentioning
confidence: 99%